Contribution of Pondok Pesantren Tahfiz Al-Qur’an in Responding to the Digital Era in South Borneo - Setiawan, Agus; Rasyidi, Ahyar (Borneo International Journal of Islamic Studies, 2020)
Negative exposure to children's dependence on devices, mobile phones, laptops and online games can indirectly damage children's education in the digital age. The digital age is accompanied by a disruptive era that permeates the life of Education, not only in schools but even in their respective homes. Of course this is troubling parents for the educational life of children. Faced with these problems, some parents began to equip their children's education with the education of the Koran from an early age. Currently, the parents' choice is in Islamic boarding schools that teach the values of Islamic education or more specifically in the education of tahfizh al-Qur'an. This study aims to analyze and map contributionsIslamic Boarding School Tahfizh Al-Qur'an Al-Ihsan Bentok and public perception of the existence of Islamic Boarding School Tahfizh Al-Qur'an Al-Ihsan Bentokin the alpha generation in the digital age. This research design uses qualitative research with approach phenomenological and sociological. Sources of data from a number of respondents randomly sampled. The results in this study describe thatIslamic Education Center Tahfizh Al-Qur'an Al-Ihsan Bentokhas carried out an important role in the form of al-Qura'n education and Islamic education which concentrated on the field of tahfizh al-Qur'an especially children who entered the alpha generation. In the aspect of education, thatIslamic Education Center Tahfizh Al-Qur'an Al-Ihsan Bentokwhich is taught contributes to personality and character, so that it is able to realize it in everyday life. The contribution to the religious aspect is to print memorization of the Koran, while the social aspect of the community is to contribute to the implementation of Islamic education, as well as to protect poor students in the form of education and guidance.